Vaccinium myrtillus L. ameliorates diabetic nephropathy via modulating metabolites and gut microbiota in rats - Cao, Xinxin; Yao, Fan; Liu, Wenxiu; Wang, Yufang; Zhang, Zhen; Zhang, Chongyang; Dong, Zhengqi; Zhang, Bin; He, Ruikun; Sun, Xiaobo (Frontiers in Pharmacology, 2025)
IntroductionDiabetic nephropathy (DN), one of the serious complications in the diabetes, has a high mortality in the diabetic patients. Bilberry (Vaccinium myrtillus L.) have received much attention for their health benefits in alleviating metabolic diseases, which are rich in anthocyanins. However, the anti-DN ability of bilberry has not been fully studied. The aim of this study was to investigate the effect and mechanism of Vaccinium myrtillus L. extract (VCE) on diabetic nephropathy in vivo and in vitro.MethodsStreptozocin (STZ) combined with high fat induced DN model was established in rats. Biochemical indicators, histopathology, 16s third generation sequencing and serum metabolomics were used to evaluate the effects of VCE on DN. Subsequently, a cell model of advanced glycation end products (AGEs) induced podocyte injury was established to verify which compounds in VCE played the main anti-diabetic nephropathy function and the mechanism of action. Finally, in vitro experiments were conducted to verify the effect of characteristic metabolites screened by serum metabolomics on improving diabetic nephropathy.ResultsInsulin resistance index, lipid metabolism, oxidative stress and inflammatory response indexes of DN rats were significantly improved after 8 weeks of VCE treatment. In addition, intake of VCE modulates gut microbiota composition and reverses the abundance of Lactobacillus, Bifidobacterium and Ruminococcus. Supplementation with VCE altered serum metabolite levels, including uridine and phenylacetylglycine. Pretreatment with VCE and its anthocyanins inhibited the expression of LDH, IL-6 and TNF-α, reduced the levels of p38-MAPK, IĸBα, IKKβ, and NF-κB in podocyte cells. In addition, pretreatment with serum metabolite uridine also reduced the expression of LDH and mitochondrial ROS, and inhibited cell apoptosis.ConclusionOur findings suggest that the improvement of gut microbiota and metabolic function were related to the anti-DN potential of VCE, and the underlying mechanism may be related to the inhibition of MAPK/NF-κB signaling pathway.